Clinical implementation of multisequence MRI‐based adaptive intracavitary brachytherapy for cervix cancer. (8th January 2016) - Zoberi, Jacqueline E.; Garcia‐Ramirez, Jose; Hu, Yanle; Sun, Baozhou; Bertelsman, Carol G.; Dyk, Pawel; Schwarz, Julie K.; Grigsby, Perry W.
Abstract : The purpose of this study was to describe the clinical implementation of a magnetic resonance image (MRI)‐based approach for adaptive intracavitary brachytherapy (ICBT) of cervix cancer patients. Patients were implanted with titanium tandem and colpostats. MR imaging was performed on a 1.5‐T Philips scanner using T2‐weighted (T2W), proton‐density weighted (PDW), and diffusion‐weighted (DW) imaging sequences. Apparent diffusion coefficient (ADC) maps were generated from the DW images. All images were fused. T2W images were used for the definition of organs at risk (OARs) and dose points. ADC maps in conjunction with T2W images were used for target delineation. PDW images were used for applicator definition. Forward treatment planning was performed using standard source distribution rules normalized to Point A. Point doses and dose‐volume parameters for the tumor and OARs were exported to an automated dose‐tracking application. Brachytherapy doses were adapted for tumor shrinkage and OAR variations during the course of therapy. The MRI‐based ICBT approach described here has been clinically implemented and is carried out for each brachytherapy fraction. Total procedure time from patient preparation to delivery of treatment is typically 2 hrs. Implementation of our technique for structure delineation, applicator definition, dose tracking, and adaptation is demonstrated using treated patient examples. Based on published recommendations and our clinical experience in the radiation treatment of cervix cancer patients, we have refined our standard approach to ICBT by 1) incorporating a multisequence MRI technique for improved visualization of the target, OARs, and applicator, and by 2) implementing dose adaptation by use of automated dose tracking tools. PACS numbers: 87.61.‐c, 87.53.Jw, 87.19.xj